2019
DOI: 10.9734/ejnfs/2019/v9i430079
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Sensory Properties of Ice Cream as Influenced by Pulse Protein Concentrates

Abstract: Pulses are one of the cheapest sources for the extraction of protein concentrates which can be gainfully utilized for meeting protein needs of specific groups. Techniques for maximum extraction of Pulse protein concentrates were developed for red gram and Bengal gram by standardisation of process parameters involving alkaline extraction followed by isoelectric precipitation. Extraction conditions viz., flour: water ratio – 1:10, pH 9 and stirring time- 4 hours were employed for isolation of the pulse protein c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Sivasankari et al. (2019) reported that, as the proportion of chickpea and pea protein increased, the pH values of ice creams increased. A positive correlation was found between the pea protein isolate and the protein contents of the samples.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sivasankari et al. (2019) reported that, as the proportion of chickpea and pea protein increased, the pH values of ice creams increased. A positive correlation was found between the pea protein isolate and the protein contents of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results obtained byAkesowan (2009) in ice cream with soybean protein isolate. a* and b* values of the samples increased with the increase of pea protein isolate due to its greenish brown color (p < .05) Sivasankari et al (2019). reported that with the increase in pulses protein concentration, the a* and b* values of ice creams increased.…”
mentioning
confidence: 89%
See 3 more Smart Citations